Acute and long‐term outcomes after polytetrafluoroethylene or pericardium covered stenting for grade 3 coronary artery perforations: Insights from G3‐CAP registry. Issue 7 (23rd September 2018) - Pavani, Marco; Cerrato, Enrico; Latib, Azeem; Ryan, Nicola; Calcagno, Simone; Rolfo, Cristina; Ugo, Fabrizio; Ielasi, Alfonso; Escaned, Javier; Tespili, Maurizio; Conrotto, Federico; Mancone, Massimo; et al.
Abstract: Background: Covered stent (CS) implantation is considered a useful device in the setting of Grade III Coronary Perforation (G3CP), one of the most harmful PCI complication. However, data regarding efficacy of this device and clinical outcomes are still limited. Methods and results: From 1993 to 2015, among 97, 779 patients from 9 European centres undergoing PCI, 224 patients had G3CP (0.23%), and 102 patients were managed with CS implantation (96 with PTFE, 6 with pericardium). Device oriented composite endpoint (DOCE), a composite of cardiac death, target lesion revascularization, and stent thrombosis (ST) in‐hospital and at long term follow‐up were evaluated. G3‐CP perforations were successfully sealed with CS in 88 patients (86.3%) with need of intraprocedural pericardiocentesis in one‐third of cases. Protamine as heparin reversal agent was administered in 36 (35%) of cases. The cumulative incidence of in‐hospital DOCE were 16.6% (17/102): death 14.7%, TLR 2.9%, ST 3.9%. At long‐term follow‐up (mean 42 ± 38 months), DOCE rates occurred in 19.7%: death 7.4%, TLR 11%, and ST 6.2%. Indication to Dual Antiplatelet Therapy (DAPT) was lifelong in 20% of cases, 1 to 6 months in 22.5% and 12‐months in 57.5% without differences in long‐term DOCE before and after DAPT interruption (8.0 vs. 6.6%, respectively, P  = 0.20). Conclusions: Use of CS was successful in sealing grade 3 coronary artery perforations in the majority of cases. Beside the high rate of clinical events at short and long‐term, ST remains the leading cause of device failure.